An investigation of semisolid Al7075 feedstock billet produced by a gas-assisted direct thermal method - Nur Azhani, Abd Razak; Asnul Hadi, Ahmad; Mohd Maarof, Rashidi; Naher, Sumsun (Springer Link, 2021)
Semisolid metal (SSM) processing is a forming process which occurs within solidus and liquidus temperatures, and it requires feedstock billets with spheroidal microstructures. In this paper, a novel gas-assisted direct thermal method (DTM) is proposed as a method to create feedstock billets with fine spheroidal microstructures. Effect of different combination parameters between pouring temperature and holding time during the gas-assisted DTM technique on the microstructure of aluminium alloy 7075 feedstock billets was investigated. Pouring of molten aluminium alloy 7075 was conducted at temperatures between 645 and 685 °C, while holding time was set between 20 and 60 s. The melt was cooled down within the semisolid temperature range in a cylindrical copper mould with the help of carbon dioxide (CO2) gas before quenching in room temperature water. Results revealed that the smallest primary phase grain size formed at the combination parameters of 645 °C pouring temperature and 20-s holding time. Furthermore, the same combination parameters also produced the highest circularity value. The addition of external CO2 gas surrounded the copper mould as a rapid cooling agent was found to have a significant improvement of 36.4% to the formation of smaller primary grain and spheroidal structure. It is concluded that the lowest pouring temperature and shortest holding time coupled with rapid cooling condition from the addition of external CO2 during DTM produced the finest and most globular structure of primary phase size.